Changing Dynamics of SARS-CoV-2: A Global Challenge - Ananya Chugh; Nimisha Khurana; Kangna Verma; Ishita Sehgal; Rajan Rolta; Pranjal Vats; Rajendra Phartyal; Deeksha Salaria; Neha Kaushik; Eun Ha Choi; Mansi Verma; Nagendra Kumar Kaushik (Applied Sciences, 2022)
Since November 2019, SARS-CoV-2 has been a matter of global concern due to its rapid spread, the millions of deaths it caused, and repeated waves of infections. One after another, many variants of this novel virus have come into existence due to its constant mutability, specifically in the spike glycoprotein region. The tally for variants of concern (VOCs), which already include Alpha (B.1.1.7), Beta (B.1.351), Gamma (P.1) and Delta (B.1.617.2), has increased to five with the latest appearance of Omicron (B.1.1.529). In our study, we examine the effect of the transmissibility and infectious potential of the virus due to various mutations of SARS-CoV-2, especially in the receptor-binding domain (RBD). We discuss the role of genome sequencing in tracing all the mutations and the importance of the R value (reproductive number) to understand the virus spread. We also review the effectiveness of the available vaccines on the variants of concern, as the rapid spread of the newly emergent Omicron variant has raised doubts about the usefulness of the current vaccines. The use of a mixed vaccination strategy has proved to be effective, yet the newer variants, such as Omicron, demand booster doses for the population. Multivalent immunogens could be considered as the plausible solution for conferring protection against potential new mutants of the virus in the future.